Lung-dominant connective tissue disease among patients with interstitial lung disease: prevalence, functional stability, and common extrathoracic features - Pereira, Daniel Antunes Silva (Sociedade Brasileira de Pneumologia e Tisiologia, 2015)

(untitled) (J Bras Pneumol)
OBJECTIVE: To describe the characteristics of a cohort of patients with lung-dominant connective tissue disease (LD-CTD). METHODS: This was a retrospective study of patients with interstitial lung disease (ILD), positive antinuclear antibody (ANA) results (≥ 1/320), with or without specific autoantibodies, and at least one clinical feature suggestive of connective tissue disease (CTD). RESULTS: Of the 1,998 patients screened, 52 initially met the criteria for a diagnosis of LD-CTD: 37% were male; the mean age at diagnosis was 56 years; and the median follow-up period was 48 months. During follow-up, 8 patients met the criteria for a definitive diagnosis of a CTD. The remaining 44 patients comprised the LD-CTD group, in which the most prevalent extrathoracic features were arthralgia, gastroesophageal reflux disease, and Raynaud's phenomenon. The most prevalent autoantibodies in this group were ANA (89%) and anti-SSA (anti-Ro, 27%). The mean baseline and final FVC was 69.5% and 74.0% of the predicted values, respectively (p > 0.05). Nonspecific interstitial pneumonia and usual interstitial pneumonia patterns were found in 45% and 9% of HRCT scans, respectively; 36% of the scans were unclassifiable. A similar prevalence was noted in histological samples. Diffuse esophageal dilatation was identified in 52% of HRCT scans. Nailfold capillaroscopy was performed in 22 patients; 17 showed a scleroderma pattern. CONCLUSIONS: In our LD-CTD group, there was predominance of females and the patients showed mild spirometric abnormalities at diagnosis, with differing underlying ILD patterns that were mostly unclassifiable on HRCT and by histology. We found functional stability on follow-up. Esophageal dilatation on HRCT and scleroderma pattern on nailfold capillaroscopy were frequent findings and might come to serve as diagnostic criteria.